2005
DOI: 10.4319/lo.2005.50.2.0646
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical cycling in the oligotrophic ocean: Redfield and non-Redfield models

Abstract: The assumption of fixed elemental ratios in ocean biogeochemical models was tested using the Hawaii Ocean Time-Series data set from the subtropical North Pacific Ocean, where nutrient-starvation is a permanent condition for near-surface phytoplankton populations. Two three-element (C, N, P) ecosystem models were coupled to a mixed-layer model, an inorganic carbon chemistry model, and dynamic pools of dissolved organic C, N, and P. One model has fixed Redfield ratios for phytoplankton (constant ratio model, CRM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 40 publications
3
42
1
1
Order By: Relevance
“…Shifts in marine C : P ratios in organic settling debris of only 30% (i.e., from the Redfield ratio of 106 to 138) result in globally significant shifts of C storage in ocean deep waters (Broecker 1982;Heinze et al 1991). Allowing for variable seston C : N : P ratios improves modeling of mixed-layer dynamics in the subtropical surface ocean (Christian 2005), suggesting variable ratios must be considered to capture certain aspects of system dynamics. All of the above questions are potentially crucial in understanding atmospheric CO 2 uptake into aquatic ecosystems, sinking flux of fixed C, and, potentially, the long-term storage of C in marine and fresh waters (Heinze et al 1991;Riebesell et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shifts in marine C : P ratios in organic settling debris of only 30% (i.e., from the Redfield ratio of 106 to 138) result in globally significant shifts of C storage in ocean deep waters (Broecker 1982;Heinze et al 1991). Allowing for variable seston C : N : P ratios improves modeling of mixed-layer dynamics in the subtropical surface ocean (Christian 2005), suggesting variable ratios must be considered to capture certain aspects of system dynamics. All of the above questions are potentially crucial in understanding atmospheric CO 2 uptake into aquatic ecosystems, sinking flux of fixed C, and, potentially, the long-term storage of C in marine and fresh waters (Heinze et al 1991;Riebesell et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, freshwater systems exhibit greater variability of seston C : N : P ratios (Hecky et al 1993;Elser et al 2000), variation that has been shown to affect patterns of nutrient cycling, secondary production, and community structure (Sterner and Elser 2002;Hessen 2005;Hessen and Elser 2005). Couplings of C, N, and P bear strongly on issues such as the biological pump (Sigman and Boyle 2000;Omta et al 2006), consumer-driven recycling processes (Urabe 1993), secondary production (Demott 2003), and the efficiency of carbon sequestration (Hessen et al 2004;Christian 2005). …”
mentioning
confidence: 99%
“…For example, at BATS (Salihoglu et al, 2008) and at HOT in the North Pacific subtropical gyre (Christian, 2005), the importance of the Dissolved Organic Phosphorus (DOP) has been demonstrated using modelling and in situ measurements. The DOP can sustain the level of primary production in these nitrogen and phosphorus limited regions.…”
Section: Role Of Don In Sustaining Primary Production In the North Atmentioning
confidence: 99%
“…It has been shown that including variable stoichiometry in ocean biogeochemistry models better represent important processes, especially those related to vertical and seasonal C cycling, than using a fixed C:N:P proportionality (Klausmeier et al, 2004;Christian, 2005). Flynn et al (2010) emphasize that the importance of nutrient limitation on changes in phytoplankton stoichiometry cannot be described by traditional models with fixed proportionality, and that this constraint has implications for modelling not only the nonlimiting nutrients, but also for understanding predator-prey interactions and nutrient recycling.…”
mentioning
confidence: 99%